Pengaruh Profitabilitas dan Likuiditas Terhadap Kebijakan Dividen Pada PT. Sepatu Bata TBK - I Gusti Ayu Diah Dhyanasaridewi; Ni Made Artini (Institut Teknologi dan Bisnis Swadharma, 2020)
Dividend policy is one of the functions of financial management apart from investment and funding decisions made by companies or banks in making decisions about the profits they receive to be distributed to shareholders according to the shares they own as dividends or reinvested as retained earnings which are carried out based on the General Meeting. Shareholders (GMS). Gitman, L.J. (2009: 611) states that